Kualitas Hidup Suami Dengan Istri Yang Bekerja Sebagai Buruh Migran - Muhammad Mu'in; Erika O.D Isgiantika (Master of Nursing, Faculty of Medicine, Universitas Diponegoro, Indonesia, 2018)
Some Indonesian women have to work as migrant worker in foreign countries because of many reasons, especially economic problem. They should leave spouse and family to fullfill live needs. Husband and children, the closest people, is the most impacted and should adapt to inexistence of wife and/ or mother. This lead to disruption to all spouse and family dimensions of quality of life. This study aimed to describe quality of life among husband whose wife were migrant worker in foreign country who have 1-18 years children. The study conducted in a village in Kendal District, Central Java. Total sampling technique were taken consist of 75 husbands. The study showed that mean score of physical dimension of quality of life was 56, psychology 43, social 44 and environment 34. Some dimensions of quality of life illustrated in this study are expected to be the initial data for further research on the problems and needs of migrant workers' families as well as input for the development of programs to meet the needs of families left by their wives and / or mothers as migrant workers.